'They're not witches. …' Young children and their parents' perceptions and experiences of Child and Adolescent Mental Health Services. (5th June 2014) - Bone, C.; O'Reilly, M.; Karim, K.; Vostanis, P.
Abstract Background Recent initiatives have emphasized the ongoing need to include children in healthcare research, which is relevant to the development of both paediatric and mental healthcare services. Our aim was to contribute children and their parents' perceptions and experiences of Child and Adolescent Mental Health Services (CAMHS), with the objective of providing guidance for those wishing to improve inclusivity and empowerment. Method We performed a thematic analysis of interview data taken from 11 children (9 boys, 2 girls, aged 8–12) and their parents (12 mothers, 2 fathers), who had recently been referred to CAMHS for mental health and educational problems. Results Three core themes emerged from the data. Fear of the unknown refers to emotional apprehension due to uncertainty of what happens in CAMHS. However children also provided useful reassurances for future service users. Therapeutic engagement refers to the importance of being listened to and building up good relationships with professionals. Finally making services acceptable was discussed in terms of issues of accessibility, session tolerances and suggestions for the development of child‐centred services. Conclusions Children were able to provide potentially useful opinions of CAMHS. In a time of limited resources it is imperative that the voices of children and their parents are acknowledged in order to improve accessibility and experiences within CAMHS.